Application of Force-Moment Sensors in Manipulator Control Systems - I. N. Scherbak (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper reveals an application of force-moment sensors in manipulator control systems. Maintenance of contact between an object and a manipulator is rather complicated task and it does not have definitive solution. The paper contains mathematical description of various manipulator control methods with application of feedback force loop. Regimes of manipulator control are changeable in accordance with the problem which is to be solved.